A metric lifting theorem - De Bondt, Ben; Vignati, Alessandro (Comptes Rendus. Mathématique, 2025)
In a recent article Farah and the authors proved a strong lifting theorem for well-behaved maps between reduced products of discrete structures, under the assumption of fairly mild Forcing Axioms. In this note, we prove the analogue of this result in the metric setting.